Variation in oil and its major constituents due to season and stage of the crop in Java citronella (Cymhopogon winterianus Jowitt.) - Sarma, T C (Journal of Spices and Aromatic Crops, 2002)
Variations in citronella oil and its major constituents due to seasonal changes and stage of the crop were studied for three years under the climatic conditions of Jorhat, Assam. Rainfall, temperature .. sunshine and relative humidity have cumulative effect on the oil yield and its major constituents namely, citronellal, citronellol and geraniol. Post monsoon months were seemed to be favourable, contributing higher oil yield. Citronellal content was higher during September (44.3%) and October (45.7%). It was observed that light rainfall (100 to 200 mm), moderate temperature (20-30oC), sunshine hours of 5 to 6 hours and high humidity (90-95%) wet:e the favourable meteorological ,parameters for higher oil yield and citronellal content in citronella oiL Growing period or stage of crop growth also had profound effect on the oil yield and citronellal content. Older crop with highly matured leaves found to yield higher oil and less citronella!. Alcohol content in citronella oil was not affected by seasonal variation. However, total alcohol percentage was found to reduce, while aldehyde percentage increased.